Filsafat Moral Fahruddin Faiz: Sintesis Al-Ghazali, Kohlberg, dan Hans Jonas sebagai Fondasi Pendidikan Karakter - M Mahbubi (UPT Publikasi Ilmiah, 2026)
This article examines the moral philosophy of Fahruddin Faiz as articulated in his work Filsafat Moral: Dari Al-Ghazali, Pakubuwana IV, Lawrence Kohlberg, hingga Hans Jonas (Mizan, 2024). Using a qualitative library research method with a critical-comparative analytical approach, this study argues that Faiz constructs an original triadic synthesis — integrating Al-Ghazali's ethics of spiritual transformation (akhlaq), Kohlberg's staged theory of moral development, and Hans Jonas's ethics of responsibility (Verantwortungsethik) — as a comprehensive foundation for contemporary Islamic character education. The findings reveal that this synthesis systematically addresses the limitations of each theory: Al-Ghazali provides transcendental depth, Kohlberg contributes systematic cognitive scaffolding, and Jonas extends both with a futuristic orientation of responsibility toward coming generations. Together, they form a three-dimensional moral model — vertically transcendental, horizontally rational, and temporally futuristic — that transcends the Islam-West dichotomy. This model carries significant implications for reformulating character education in Indonesian Islamic educational institutions, particularly pesantren-based universities.